TEACHING STRATEGY TO PROMOTE STUDENTS SPEAKING SKILL IN EXTRACURRICULAR OF THE 2nd GRADE AT AZMANIA BOARDING SCHOOL IN THE ACADEMIC YEAR OF 2018/2019 - Risa Stiowati; Risqi Ekanti A Palupi; Siti Asiyah (Universitas Muhammadiyah Ponorogo, 2019)
Speaking is one of the most important skills in communication that should be learned by the people. By speaking, the people combine information and ideas by communicating with each other. Extracurricular is one of ways to learn English. By following English extracurricular, the students can increase their speaking skill ability. All of students at Azmania Boarding School also follow the English extracurricular. Therefore, when they are in second grade, they are able to use English in their daily lives. The purpose of this study was to analyze the teaching strategy to promote students speaking skill in English extracurricular of the 2nd grade and the implementation of the strategy at Azmania Boarding School of Ponorogo in the academic year of 2018/2019. This research design was qualitative research of case study. As the data collection techniques, the researcher used qualitative observation and interview. The subject of this research was the instructor of the second grade’s English extracurricular. Based on finding and discussion, the teacher’s activities in classroom were learning by playing, singing and telling. Those activities were categorized as Active Learning strategy. This strategy gave good effect for the students. This strategy also increased students’ motivation in speaking skill. The implementation of this strategy was by combining materials with song, story and game. The implementation of this strategy also based on the students’ need. Based on the results of the study, the researcher gives suggestion related to the strategy of teaching speaking. For teachers, it is hoped that this research can encourage other teachers to adopt this strategy. Besides adopting this strategy, other teacher can modify this strategy to improve speaking skill of the students. The teacher also can apply interesting strategies to develop the students’ ability. By using various strategies in teaching, it is hoped that the students are not bored and get good way to improve students speaking skill. For students, they need to increase their motivation and interest in learning English. They need to practice speaking skill in their activity. Students can use media in around them, for examples; song, story or novel, games, etc. to improve their speaking ability. The last for other researcher, the researcher hopes that the other researcher can do some improvement in many aspects that can be analyzed in English language especially in speaking skill.